Quality of nursing work life and associated factors in Amhara Region Referral Hospitals, Northwest Ethiopia: A cross sectional study - Henok Biresaw; Berhanu Boru; Bezenaw Yimer (Elsevier, 2020)
Background: Quality of nursing work life is the degree to which nurses are satisfied with their personal needs; while achieving their organizational goals, which in turn, leads to an increase in their to increase the productivity and reduces turnover rate and psycho-social impact. Thus, this study aimed to assess the quality of nursing work life and associated factors in Amhara Region Referral Hospitals, Northwest Ethiopia. Methods: Institution based cross-sectional study design was used among 461 nurses working in Northwest Ethiopia. Data were collected by a pre-tested, self-administered questionnaire of Brook's and Wisconsin Quality of Life Index. Data were entered into SPSS version 22 for calculation of descriptive, inferential statistics and binary logistic regression. Binary logistic regression was utilized to identify factors associated with the quality of nursing work life. Adjusted odds ratio with 95% confidence interval was computed to determine the level of significance. Results: Overall, the quality of good nursing work life was found to be 40.8%. Factors such as: public image of a society (AOD = 5.55, 95%CI: 2.39-12.84), nursing position (AOR = 3.01, 95%CI: 1.63-8.25), working department (AOR = 4.13, 95% CI: 1.06-16.1), educational status [ (AOR: 2.36, 95%CI: 1.20-4.66)], availability of safe place to rest (AOR = 2.01, 95%CI: 1.07-3.75) and availability of a safe drinking water (AOR = 2.33, 95%CI: 1.24-4.37) were associated with a good quality of nursing work life. Conclusion: More than half of the nurses in Ethiopian study had poor quality of work life. Therefore, nurses are suggested to strengthen their educational status and their awareness toward community perceptions of nursing. Higher officials are also suggested to improve the working environments of nursing.